(untitled) (FAVE Sección Ciencias Agrarias, 2021)
The constant and excessive use of synthetic fungicides in fruit and vegetable industry has caused dangerous environmentally changes and deeply affected human health. In this context, exploring natural antifungal sources represents an economic and environmental importance. It was proposed to study the activity of ﬁve volatile oils obtained from the native plant species Dysphania ambrosioides, Baccharis frenguellii, Baccharis salicifolia, Lippia alba and Lippia turbinata against phytopathogenic fungi belonging to the genus Botrytis, Colletotrichum, Rhizopus, Fusarium and Monilinia isolated from infected strawberries and peaches. The assays were carried out using the agar diffusion method adapted for volatile samples and the percentages of fungal inhibition were determined for each sample using ImageJ® software. The chemical proﬁle of each essential oil was analyzed by GC-MS and the majority compounds were determined. Results showed a high antifungal potential for all the samples evaluated, particularly the product obtained from L. alba.